Correlation of ultrasonography, hysterosalpingography and hystero-laparoscopy findings in cases of infertility - Shaikh, Falahunisa S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Infertility is a condition which has medical as well as social impact on the state of the couple. Approximately 10-15% couples are infertile. A wide arena of tests is available for the diagnosis of the causes of infertility. The aim of present study is to correlate the findings of ultrasonography, hysterosalpingography and hysterolaparoscopy in infertility. Methods: It is a prospective study done over 2 years at INHS Asvini hospital, Mumbai. Infertile women underwent ultrasonography, hysterosalpingography and hystero-laparoscopy. Data was assessed using SPSS 17 software. Results: Of 105 patients, on ultrasonography, 22.9% had Polycystic ovaries (PCO), 2.9% had ovarian cyst, 4.8% had fibroid, 4.8% had endometrioma, 3.8% had adnexal mass, 3.8% had polyp. On hysterosalpingography, 18 (17.1%) had left and 20 (19%) had right tubal block, 11 (10.47%) had B/L tubal block, 6 (5.7%) had septate uterus, 6 (5.7%) had hydrosalpinx. On laparoscopy, 12 (11.4%) had PCO, 4 (3.8%) had ovarian cyst, 12 (11.4%) had fibroid, 7 (6.7%) had endometrioma, 19 (18.1%) had left and 18 (17.1%) had right tubal block, 12 (11.42%) had B/L tubal block, 4 (3.8%) had hydrosalpinx. On hysteroscopy, 7 (6.7%) had septate uterus, no polyp seen. On laparoscopy, 21 (20%) had endometriosis, 1 (1.9%) had bicornuate uterus. Conclusions: On comparing the results it was observed that hysterolaparoscopy gives definitive diagnosis and should be considered gold standard, though other modalities of investigation should be considered complimentary and not competing with it, as they are noninvasive.